What Do Multinational Firms Want from Cities? : Competitive Cities for Jobs and Growth, Companion Paper 5 - Zhu, T. Juni; Aranda Larrey, Yago; Santos, Valerie-Joy (World Bank, Washington, DC, 2016)
The objective of this paper is to understand the factors driving the location decisions of multinational corporations. The paper uses literature-review and expert-interview techniques to understand what cities can do to be best positioned to attract international capital.